The student as true learner in the mathematics education study program - Nanda Arista Rizki; Gyta Krisdiana Cahyaningrum (Primatika : Jurnal Pendidikan Matematika, 2026)
This study aimed to describe the character of a student with the greatest outdegree in Social Network Analysis (SNA) based on their group study partners. This research took 111 active students in the mathematics education study program at Universitas Mulawarman who were still taking courses. Research instrument in the form of a questionnaire name and NIM study friends. After forming the SNA structure, then select the node with the greatest outdegree and declare him/her as the true learner. This research used mixed methods, which means the researcher also interviewed the student declared as the node with the greatest outdegree. Based on the results, a student with NIM 2005046073 has the greatest outdegree of 22. This student was very active in asking her friends about the lecture material and their opinions regarding her understanding of the material. Furthermore, the student also gave tips on becoming a true learner on campus.